A case report of drug rash with eosinophilia and systemic symptoms in a patient using carbamazepine - Zand, Amin (Researcher Bulletin of Medical Sciences, 2018)
Drug rash with eosinophilia and systemic symptoms (DRESS) is a critical type of drug reaction with signs such as fever, skin rash, lymphadenopathy, hematological abnormalities particularly eosinophilia, and internal organ involvement like hepatitis two to eight weeks after a drug is first used. The present case is an example of hepatitis as a manifestation of drug reaction with eosinophilia and systemic symptoms syndrome. Case Presentation A 17 year-old man is reported as a known case of epilepsy from childhood, who presented anti-epileptic-induced “drug reaction with eosinophilia and systemic symptoms syndrome” with a seven-day history of pruritic rash, periorbital, face and upper extremities edema, hepatitis and fever was admitted at Loghman Hakim Hospital in Tehran, Iran in December, 2015. Laboratory tests showed an eosinophilia and elevated serum liver enzymes. The patient's history showed no drug allergies, but five weeks prior to hospital admission, his therapy regimen had been changed from sodium-valproate to carbamazepine. Carbamazepine was discontinued on hospital admission, and after nine days of high-dose corticosteroid therapy the patient's symptoms and laboratory markers were stable. Conclusion Given the high morbidity and mortality rate of DRESS syndrome, physicians should bear in mind this severe hypersensitivity reaction particularly when starting anti-epileptic drugs. Early diagnosis of drug reaction with eosinophilia and systemic symptoms syndrome and initiation of appropriate treatment plays a key role in limiting morbidity and mortality.